Progetti di territorio La costruzione di nuove tecniche di rappresentazione nei Sistemi Informativi Territoriali - Carta, Massimo (Scuole di dottorato, 2005)
The research is aimed at investigating the changes in the methods of "construction" of representations of the territory due to the communicative evolution of disciplinary statutes and to the increasingly stringent and widespread use of new information and communication technologies. It focuses its reflection on the field of representations intended to substantiate the local and territorial project dimension. The focus of the work is on the methodological value and possible process innovation, rather than on the simple description of an expert technical product. The emphasis is on the possible value of building knowledge of territorial representations (heritage elaborations or project scenarios) drawn up through collective action.